Epidemiology and temporal patterns of burn-related emergency medical services missions in southern Iran: a five-year population-based registry study - Mahmoudreza Peyravi; Milad Ahmadi Marzaleh; Marziyeh Hamyali-Ainvand (BMC Emergency Medicine, 2026)
Abstract Background Burn injuries remain a major cause of injury-related morbidity and mortality worldwide, particularly in low- and middle-income countries. Although Emergency Medical Services (EMS) are often the first point of professional care for patients with burn-related emergencies, population-based evidence describing the epidemiology and prehospital management of EMS-attended burn-related emergencies remains limited. This study aimed to describe the epidemiological characteristics, temporal patterns, burn mechanisms, annual incidence, and EMS mission dispositions of burn-related EMS missions in southern Iran over a five-year period. Methods This province-wide population-based retrospective cross-sectional registry study analyzed routinely collected EMS data from Fars Province, southern Iran. All burn-related EMS missions recorded between March 2020 and March 2025 were included. Demographic characteristics, burn mechanisms, temporal patterns, EMS mission dispositions, and annual incidence rates were analyzed. Associations between categorical variables were assessed using Pearson’s chi-square test, whereas age distributions were compared using the Kruskal–Wallis test. Temporal trends in annual incidence were evaluated using Poisson regression with the provincial population included as an offset variable. Results A total of 5,469 burn-related EMS missions were analyzed. The mean patient age was 33.65 ± 16.59 years, and 75.5% were male. Flame burns were the most common burn mechanism (45.1%), followed by electrical injury-related EMS missions (25.3%). Burn mechanisms differed significantly according to sex, age group, season, time of EMS activation, calendar year, and EMS mission disposition (all P < 0.001). After adjustment for annual population size, the incidence of burn-related EMS missions increased significantly during the study period (incidence rate ratio [IRR] = 1.08, 95% CI 1.06–1.10; P < 0.001). Overall, 66.2% of patients were transported to a medical facility, whereas 17.8% received on-scene treatment with referral recommendations, 14.2% declined transport, and 1.8% were deceased before or upon EMS arrival. Conclusions This province-wide registry study demonstrates the complementary value of prehospital EMS data for burn epidemiology. Distinct demographic, temporal, and mechanism-specific patterns were identified. Linking EMS and hospital registries will strengthen burn surveillance and improve evidence for prevention, EMS planning, and burn care.